Integration of Philosophical Thinking Methods to Encourage Deep Learning Achievement in Educational Units - T, Marini; Wijaya, Mulyadi; Saifullah, Saifullah (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The lack of learning methods offered in classrooms has caused a slowdown in the development of students' reasoning skills in educational units.Purpose. exploring philosophical approaches as a conceptual framework for developing students' critical, analytical, and reflective thinking skills.Method. The method used in this writing is a literature study, by tracing various references related to the topics discussed in this study. This study highlights the importance of Ontology, Epistemology, Axiology in building a deep conceptual understanding for students in educational units. By using theoretical analysis and an interdisciplinary approach.Results. The results of the study show that philosophical thinking methods can encourage the search for meaning, the development of logical arguments, and the integration of ethical values in the learning process.Conclusion. Philosophy-based learning encourages active participation of students, strengthens their ability to contextualize knowledge, and increases their intrinsic motivation for lifelong learning.